PENDAMPINGAN PRODUKSI MaMiN BERBAHAN BAKU DAUN KELOR PADA KELOMPOK KADER ODGJ - Sri Rulianah; Prayitno Prayitno; Sugeng Hadi Susilo; Nurul Hidayatinnisa (P3M Politeknik Negeri Malang, 2023)
The ODJG group (People in Mental Disorders) is a community group engaged in social activities: helping, guidance, and mental health rehabilitation for ODJG who have undergone psychiatric medical treatment from a Mental Hospital. To carry out its activities, this group formed a business that produces food and beverages (MaMin) made from Moringa leaves (moringa tea, instant Moringa, Moringa ice wax, Moringa yogurt, Moringa pudding, Moringa flower extract). where the products have been marketed in Malang and surrounding areas. However, the production process encountered several obstacles: the lack of production equipment, the lack of maintaining product quality and the health of the work environment, and the lack of marketing techniques. Community service (PkM) aims to increase partners' ability to produce quality, safe, dan healthy MaMin made from Moringa leaves. The methods used in solving partner problems: 1). Production equipment grants, 2). Excellent and safe production technique training (GMP and HACCP), 3). Marketing digital training (digital marketing), 4). Production and marketing assistance and consulting. The results of the PkM activity show that there is an increase in the knowledge and skills of partners in producing healthy and quality MaMin and marketing it with digital marketing media